Literature and medicine: Renu's Prashant - Gandhi, Mohit P. (Research and Humanities in Medical Education, 2024)
Phanishwar Nath Renu's classic Hindi novel 'Maila Anchal' (1954), takes us through the transformative journey of a young medical graduate named Prashant. It echoes the contemporary discourse on the multiple dimensions and determinants of health.